Optimizing The Role of Religious Organizations In Basic Education In Kranggan Village - Fadila Choirul Yaumi; Ma'rifat Al Haq Syir Nur Kholiq; Adeni Adeni (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Religious organizations have a very important role in developing education, especially in rural areas. Through the various educational programs and institutions they have established, religious organizations not only improve the quality of formal education, but also play a role in shaping the character and moral values of the younger generation. Therefore, through this article we will discuss the role of religious organizations in developing education in villages. This community service program is implemented using the Asset Based Community Development (ABCD) method. ABCD was built based on the principles put forward by John McKnight and Jody Kretzmann who are also the founders of The Asset-Based Community Development (ABCD) Institute. An asset-based approach helps communities see the reality of internal conditions and possible changes that can be made. In general, religious organizations have a very important role in basic education in Kranggan village. They not only provide access to education but also play a role in shaping children's character and personality through education based on religious values.